Advances in hormonal therapies for hormone naïve and castration-resistant prostate cancers with or without previous chemotherapy. Issue 1 (December 2015) - Pham, Thy; Sadowski, Martin; Li, Huika; Richard, Derek; d'Emden, Michael; Richard, Kerry
Abstract Hormonal manipulation plays a significant role in the treatment of advanced hormone naïve prostate cancer and castration-resistant prostate cancer (CRPC) with or without previous chemotherapy. Combination of gonadotropin releasing hormone (GnRH) agonists and androgen receptor (AR) antagonists (combined androgen blockade; CAB) is the first line therapy for advanced hormone naïve prostate cancer, but current strategies are developing novel GnRH antagonists to overcome disadvantages associated with GnRH agonist monotherapy and CAB in the clinical setting. Abiraterone acetate and enzalutamide are hormonal agents currently available for patients with CRPC and are both shown to improve overall survival versus placebo. Recently, in clinical trials, testosterone has been administered in cycles with existing surgical and chemical androgen deprivation therapies (ADT) (intermittent therapy) to CRPC patients of different stages (low risk, metastatic) to abate symptoms of testosterone deficiency and reduce cost of treatment from current hormonal therapies for patients with CRPC. This review will provide an overview on the therapeutic roles of hormonal manipulation in advanced hormone naïve and castration-resistant prostate cancers, as well as the development of novel hormonal therapies currently in preclinical and clinical trials.